Monoamine oxidase B oxidizes a novel multikinase inhibitor KW-2449 to its iminium ion and aldehyde oxidase further converts it to the oxo-piperazine form in human. Issue 5 (October 2017) - Hosogi, Jun; Ohashi, Rui; Maeda, Hiroshi; Tashiro, Satoshi; Fuse, Eiichi; Yamamoto, Yorihiro; Kuwabara, Takashi
Abstract: (E)-1-4-[2-(1H-Indazol-3-yl)vinyl]benzoylpiperazine (KW-2449) is a novel multikinase inhibitor. During our clinical study, we found that KW-2449 is mainly metabolized to its oxo-piperazine form (M1). An inhibition study suggested that monoamine oxidase-B (MAO-B) oxidizes KW-2449 to an iminium (intermediate) and aldehyde oxidase (AO) then metabolizes the intermediate to M1. The conversion of KW-2449 to the iminium (intermediate) by MAO-B was confirmed by the formation of its cyanide adduct. This cooperative metabolic pathway by MAO-B and AO was newly identified in the metabolism of piperazine. The clearance of KW-2449 by MAO-B and AO in human was estimated based on the kinetic analysis with in vitro-in vivo extrapolation. The systemic clearance in human was similar to the calculated value, indicating that the extrapolation approach was applicable to KW-2449 metabolism. Finally, we found that (E)-3-amino-1-4-[2-(1H-Indazol-3-yl)vinyl]benzoyl-pyrrolidine (Compound A) as a stable compound against MAO-B and AO. The total body clearance of Compound A was reduced to one tenth of KW-2449, demonstrating that preventing the metabolism of MAO and AO led to more preferable pharmacokinetic profiles. As piperazine is often introduced to drug candidates to improve lipophilicity of the compound to get more hydrophilic nature, the results of this study provide useful information for future drug development. Graphical abstract: